Attitudes towards no-European Immigrants in EU: The Role of Legacy Media and New Media - Tomaselli, Venera; Sampugnaro, Rossana (Migration Letters, 2022)
Many studies in different scientific fields offer controversial results on the media’s role to influence attitudes towards immigration. In the present paper, the attitude that European public opinion has towards no-European immigration is analysed through data from Eurobarometer in the 3 waves starting in 2017 until the latest updated in 2019 with the aim to estimate the relationship with new and legacy media use. Specifying repeated measures multilevel models, we find that the use of legacy media (TV, press, and radio) and new media (website and online social networks) affects the relationship between citizens’ opinion in EU and attitudes towards no-European immigrants, when the European migration crisis reaches high levels and the migration issue becomes heated for public opinion. High exposure to news communication produces different relationships looking at legacy and new media. If radio, TV, newspapers are used frequently to obtain political information, the attitudes towards external migration are hostile but also in the case of new media. Legacy media manage to soften the negative attitude towards no-European immigrants, at least for low levels of immigration. On the contrary, new media are able to bring European citizens into line with even negative or hostile attitudes.